EU enlargement, migration and the new constitution - Hans-Werner Sinn (Center for Economic Studies and ifo Institute (CESifo), 2004)
The paper deals with the effects of migration resulting from EU Eastern enlargement on the welfare states of Western Europe. Although migration is good in principle, as it yields gains from trade and specialization for all countries involved, it does so only if it meets with flexible labour markets and if it is not artificially induced by gifts from the welfare state. This is not the present state of affairs in Western Europe. In addition to measures that make labour markets more flexible, the introduction of delayed integration of working migrants and the home country principle for non-working migrants is a rational reaction of the state. The proposed new EU constitution which contains far-reaching rules for a European social union should be amended accordingly.
Keywords: E2; J6; F2; H0; J3; 330; EU enlargement; migration; EU constitution; social union; Einwanderung; Internationale Arbeitsmobilität; EU-Erweiterung; Sozialstaat; Verfassung; EU-Staaten; Osteuropa